KLASIFIKASI KALIMAT PASIF INTRANSITIF DALAM BAHASA JEPANG BERDASARKAN PERAN SEMANTISNYA - Sutedi, Dedi (Universitas Muhammadiyah Surakarta, 2012)
A predicate of a passive sentence in Japanese can be filled in by a transitive,ditransitif, and intransitive verb. Passive sentences with intransitive verbs as the predicates commonly express oppositive meaning. Linguists commonly classify this type of passive sentence regarding only to its syntactical function and category. This study however investigates passive intransitive sentences regarding not only their syntactical function and category, but also their semantic construction. The study finds five types of syntactical construction of passive intransitive (I V). Each type of the passive is distinguished by the semantic information of its modifiers.